Estratégias enunciativas e a construção do ator feminino em a mulher que escreveu a bíblia - Guimarães, Valci Aparecida Xavier (2009)
This paper develops a semiotic reading of the novel A mulher que escreveu a Bíblia, written by Moacyr Scliar, through theoretical assumptions from French semiotics. We aim at describing the actor “woman” in the roles of a pragmatic, cognitive and passional subject. It is known that these roles have as modalizers the doing, the knowing and the feeling, respectively. We analyze the actor “woman” in the thematic role of subject “writer” not only at the level of the utterance but also at the level of enunciation. In the level of enunciation, the enunciator projects it at the present time, as a cognitive subject, who, by means of past lives therapy, discovers having lived in a remote time, the time of Salomon, and having been responsible for the writing of the Bible. Therefore, it is the path of this woman, as a subject of the utterance, projected in the past, the focus of our analysis. We have observed the state transformations she goes through, her performance in the writing of the Bible and the struggle to build her feminine identity, changing from object into subject of her own history. We have also examined the passional path lived by the actors, through enunciative scenes in which they let themselves be dominated by some passions, such as anger, revenge and jealousy. In this sense, we have searched to describe how such passions appear in the interaction, in the intersubjective relationship of the utterance, and how they organize themselves in the canonic passional schemes, as well. We have noticed that although the actor “woman” carries a stigma of the ugliness in a patriarchal society, ruled by prejudice, modalized by knowledge and the power of doing, builds herself as wise, fearless, and breaks the chains that used to have her stuck to submission. Nonetheless, her history would have been forgotten, had she not been recreated by the woman of the present of enunciation, since all her manuscripts had been burned in the past. This way, we have observed that the subject of enunciation creates the therapeutic process, that he overtly mocks, as an enunciative strategy to bring to life the history of the past woman, retold by the woman of the present. Thus, it is suggested that all is fiction - literary fiction - fruit of imagination. And the irony which is projected in the feminine actor is the way that is found to have a dialogue with the myths of past and present, and to reveal himself as a passional subject, admirer of the feminine cause.